Assessment of Awareness, Attitude and Performance of Surgical Team about Medicinal Plants Use by Candidate Patients for Surgery - Mehdi Ghasemzadeh Bariki; Ebrahim Nasiri; Shahnaz Barat; Hooshang Akbari (Tehran University of Medical Sciences, 2022)
Due to the increasing application of traditional and complementary medicine methods as well as medicinal herbs and given the drug interactions during surgery, the goal of this study was to determine the awareness, attitude and performance of surgical team regarding the use of herbs by surgical candidates. In this cross-sectional descriptive study, members of surgery and anesthesia team completed a data collection form, which included personal information and specialized questions (10 awareness, 9 attitudes, and 9 performance questions). The score for each awareness question was 0-2, which was 1-5 for attitude and performance questions, respectively. Quantitative data were reported with mean ±SD, and qualitative data were reported as frequency percentage. Quantitative variables were analyzed by Mann-Whitney and Kruskal-Wallis tests, and qualitative variables were assessed using Chi-square test. Among 185 participants, there were 99 women (53.6%). 31.4% of participants were specialists or assistants, 87.6% of them had moderate attitude, 82.3% showed poor performance and 82.2% poor awareness. The level of awareness was not significant in terms of specialization but that of attitude (p < 0.001) and performance (p < 0.019) was significant. Considering the growing trend of medicinal plants' consumption in people, and given the moderate attitude, as well as poor awareness and performance of surgical team members toward medicinal plants, increasing knowledge level, prevention of drug interactions and potential side effects of medicinal plants together with training planning are essential for surgical team members to increase patient safety.